Spiralling whitefly under control in South Pacific - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
A biological control measure may be able to stop the spread of the Spiralling Whitefly in the South Pacific. It has been shown that a parasitic wasp can reduce populations of the pest considerably. The Spiralling Whitefly (Aleurodicus dispersus)...